Dark Tourism as an alternative tourism development in Wang Kelian, Perlis, Malaysia - Abdullah Sani, Noorfathehah; Yusnita Yusof,; Yahaya Ahmad,; Nuraini Abdul Rahman, (Advances in Humanities and Contemporary Studies, 2024)
The purpose of this article is to provide a comprehensive analysis of tourism development in Malaysia's northernmost state of Perlis. It is located in the northernmost part of Malaysia, bordering Thailand. The study was conducted using a qualitative and quantitative survey. The data collected during the study was used to develop a strategy to improve tourism development in the state by providing an alternative type of mainstream tourism; Dark Tourism. Despite the state's potential to become a significant tourism destination, the study found that several factors have hindered the development of the tourism industry in the state. These include a lack of proper planning and development and poor maintenance of facilities.